Этносоциология: объектно-предметное поле и перспективы исследований - Евтух, В. (Социология: теория, методы, маркетинг, 2007)
The article raises some theoretical issues of the ethnosociology as a relatively new branch of sociology. The author presents definition of the ethnosociology as a science and an academic discipline for universities, its summarized history, object and subject,research methods, as well as the main lines of development in a comparative way, i.e. in the world and Ukrainian context.